Problems of coordination in field administration in Bangladesh: does information communication matter? - Ahsan, A.H.M. Kamrul; Panday, Pranab Kumar (2013)
The main thrust of the article is to analyze the state of problems of inter-organizational coordination in the upazila (second tier of local government) in Bangladesh. It also explains to what extent informal communication matters for inter-organizational coordination. Based on empirical data collected in 2009, findings of the study suggest that a number of factors have facilitated non-existence of inter-organizational coordination at the upazila. These factors include lack of division of activities, dualism in control over officers, lack of proper functioning of the committees, and dual authority in disbursement of funds and its impact on timely disbursement. Findings also suggest that in the absence of coordination among different departments, informal communication has been observed to be one of the prominent mechanisms of ensuring coordination. However, existence of factors like lack of willingness to be engaged in informal communication and lack of cooperation has hindered the process of building informal communication among different departments. Despite having some problems this research has concluded that informal communication has helped the process of coordination among different departments while they are carrying out their responsibilities. - Reproduced.
Keywords: Local government - Bangladesh; Local government